Experimental evaluation of the tension mooring effect on the response of moored ships - Paulo Rosa Santos (2014)
Tension mooring may be applied to improve operational and security conditions of exposed port terminals. This paper analyses the influence of the type of fender facing on the efficacy of tension mooring in terms of reduction of the moored ship motions and improvement of the operational and security conditions at berth. Two mooring line pretension conditions and two types of interfaces between the ship and the fenders were experimentally investigated. The physical model was designed based on the characteristics of a real port terminal with operational problems-the Leixões oil terminal, Portugal. The analysis of the moored ship response shows that high friction fender facings reduce moored ship motions and significantly increase the tension mooring efficiency. The magnitude of pretension forces and the type of ship-fenders interface are important aspects when looking at common environmental conditions, but their contribution to reduce moored ship motions during rough (extreme) conditions is limited. It was also concluded that friction forces developed at that interface provide additional damping to the dynamic system composed of the moored ship and help preventing resonance, in particular when contributions from other sources of damping are minimal, as it is shown for roll. (c) 2013 Elsevier B.V.